The Impact of Loan Loss Provision and Bank Capital on Performance in UK Banking Industry: Evidence from the 2007 Global Financial Crisis. - Akinwamide, Aarinola Esther (2015)
This paper has examined the UK's banking system, looking specifically at the structure, legislation and regulatory bodies that govern the banking system. It has analysed the loan loss provisioning practices and x-efficiencies during the period of 2008-2013. Moreover, we complement and extend existing literature because there are noticably limited literature resources' that examine cost x efficiencies in UK banking industry since the 2007 global financial crisis. The main findings of this study support that there are significant relationships between loan loss provisions and bank capital with bank profitability. It also finds that UK banks have remained fairly efficiently since the 2007 crisis intervention and that banks' with a larger total assets and tier 1 capial maintained a cost x-efficiency value that is higher than that of banks with a smaller size.